The effectiveness of growth completion of one pen, one animal and unit of gain of pure bred, mixed bred and cross bred piglets of different breeding direction - Kremez, M.; Myronenko, O.; Kuzmenko, L.; Shaferivskyi В.; Karunna, T.; Fesenko, O.; Ilchenko, M. (Scientific Progress & Innovations, 2025)
The effectiveness of growth completion of one pen, one animal, and unit of gain at pure breeding, pure line breeding, crossing and cross-breeding of maternal and paternal lines under the conditions of pork industrial production was studied in the article. It was established that the use of cross-breeding at piglets’ growth completion favored raising their growth intensity by 15.1 % and by 19.4 % of pen weight by the end of growth completion, improving feed conversion rate by 1.7 %, decreasing the cost of 1 kg of weight gain by 3.9 %. This, in its turn, affected the rise profitability level of one piglet and one pen growth completion by 18.0 % as well as the profit increase from growth completion of one piglet by 20.5 % in comparison with piglets’ pens of Large White and Landrace breeds’ crosses. The exceeding of cross bred piglets over the maternal parent forms as to one head absolute weight gain by 22.5 % and the total gains of one piglet pen by 32.3 % during growth completion period was established as well as the increase by 19.2 % of one piglet weight and by 28.6 % of pen weight at the end of growth completion period. This favored the improvement of feed conversion by 5.4 %, the decrease in the cost of 1 kg weight gain by 7.6 % and by 11.0 % of live weight at the end of growth completion, the growth of market value of one piglet by 12.7 % and the pen – by 28.6 %, the increase by 34.0 % of the income from growth completion of one piglet and by 12.5 % of 1 kg live weight, and by 44.7 % of the profitability of their pen growth completion, which affected the profitability level increase of one piglet and the pen growth completion by 26.3 % in comparison with the pens of pure-bred animals of Large White and Landrace breeds. It was established that the advantage of synthetic paternal line over cross-bred piglets concerning growth intensity during the completion reached 2.7 % and one piglet weight at the end of the period rose by 5.3 %. Feed conversion improved by 8.0 %, food consumption by one piglet during growth completion decreased 5.1 %, the operation cost of one piglet growth completion lowered by 4.5 %, the cost of 1 kg weight gain by the end of growth completion decreased by 7.4 % and market value of one piglet rose by 5.3 %. At the same time, the cross bred animals exceeded the paternal parent genotype as to the total piglet pen gains by 52.1 % during the period of growth completion, by 47.1 % – as to pen weight by the end of the period, by 62.3 % as to operation cost of piglets’ pen growth completion. The pen live weight cost at the end of completion decreased by 36.4 %; its market value rose by 47.1 %, and the profit increased by 1.9 % from one piglet growth completion, and from 1 kg live weight – by 7.6 %. The profitability of pen growing rose by 58.2 %, which favored the increase in profitability level by 16.0 % of one piglet and the pen completion in comparison with the pens of pure-bred piglets of PIC-337 synthetic paternal line